Atributos físicos e químicos de um latossolo fertirrigado com efluente de suínos - Silva, Josimar Brito da (2011)
This study aimed to evaluate the physical and chemical changes in an Oxisol fertilized with swine effluent. An experiment was conducted in a randomized design with six treatments with increasing doses of sewage. Sampling for chemical and physical analysis of the soil were made in layers of 0-30 and 0-60 cm respectively. The variables were hydraulic conductivity, bulk density, porosity (total, macro and micro), geometric mean diameter, mean weight diameter of aggregates stability index, pH, total nitrogen, phosphorus, potassium, sodium, zinc and copper available. The results indicate that the physical and chemical soil properties are strongly modified when added to swine effluent, requiring monitoring in the soil profile in order to reduce the risk of contamination and pollution of soil and subsurface waters.